Performance evaluation of a reinforced concrete building strengthened respectively by the infill wall, active and passive tuned mass damper under seismic load. (15th October 2019) - Akyürek, Osman; Suksawang, Nakin; Go, Tiauw Hiong; Tekeli, Hamide
Highlights: The infill wall can increase the the rigidity and the damping of a structure. The infill wall is the securest energy dissipater system. The infill wall is also very effective in restricting inter-story drift ratio. Abstract: One of the most commonly used control methods is a tuned mass damper (TMD), which is often employed to mitigate the amplitude of mechanical vibrations. To get a more effective response reduction of the structure, it is essential that the dynamics of the structure are modeled as accurately as possible. In this study, the seismic response of a reinforced concrete (RC) six-story building was analyzed with the combinations of masonry infill-wall, a passive and an active tuned mass damper (ATMD). The infill walls were placed along all frames without any space between column-wall and beam-wall connection. The TMD has no external source of energy, while the ATMD has an external energy source generated by the actuator which is driven by a linear quadratic regulator (LQR) controller. The dynamic response of the building was evaluated using the data from a real earthquake excitation of El Centro in 1940. The results highlight the inclusion of masonry infill wall in the seismic analysis is very important and has a substantial effect on the fundamental frequency and seismic characteristic of the structure. It also has a significant impact on the reduction of the inter-story drift and the seismic energy performance of the building.